Reviewing next of kin regrets in surgical decision-making: cross-sectional analysis of systematically searched literature - Julien Maillard; Tal S. Beckmann; Martin R. Tramèr; Nadia Elia (SpringerOpen, 2023)
Abstract Background Decision-making concerning relatives undergoing surgery is challenging. It remains unclear to what extent implicated next of kin eventually regret their decisions and how this regret is assessed. Our aim was to systematically review the literature on decisional regret of next of kin and to describe the assessment tools used and the surgical populations studied. Methods We included interventional or observational, quantitative or qualitative studies reporting the measurement of decisional regret of next of kin concerning relatives undergoing surgery. We searched a variety of databases without restriction on publication year. We assessed the quality of reporting of quantitative studies using the NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies and of qualitative studies using the Critical Appraisal Skills Program Checklist. Results Thirteen cross-sectional, five prospective cohorts and five qualitative studies matched our inclusion criteria. In 18 studies (78%), patients were children, in five (22%), young or middle-aged adults. No study included elderly or frail patients. Thirteen studies (57%) used the original Decision Regret Scale which was validated for patients, but not for next of kin. Only 3 of the 18 (17%) quantitative studies and only one of the 4 (25%) qualitative studies were rated as "good" in the quality assessment. Conclusion None of the retrieved studies used validated tools to assess the decisional regret of next of kin and none of them examined this issue in elderly or frail surgical patients.